“Gogol or Provincial in the Capital”: from Ukraine to St. Petersburg - M. S. Akimova (Научный диалог)
The article is devoted to the problem of the uniqueness of creativity of N. V. Gogol and his place in literature. The relevance of the work is determined by pendency of the issue, which literature researchers repeatedly addressed to. The author uses an interdisciplinary approach. The study is based on extensive literary material. Problem of finding the “key” to understanding the creativity and fate of N. V. Gogol rises from the lore point of view. A review of literature on the subject is given. It is shown that in the spiritual and creative fracture of the writer, and hence his growth, a significant role was played by moving from the Ukraine to Petersburg. The author dwells on the universality of Gogol as one of the national corollaries of duality, which became a fruitful imperative of his creativity, the key breakthrough - through Russian language and Russian themes - from the “provincial Dikanka” to the universal horizon. The article proves the idea that Petersburg in contrast with the Little Russia breaks (and forms) Gogol’s optics. It is noted that the writer did not remain in debt: there was “invasion of the Ukrainian wave with Gogol on the crest” in Russian culture (in the words of N. Piksanov). It is shown that the regional approach applicable to the figure of the writer allows to expand the possibilities of literary analysis. Also the question is raised about the relationship of reality and artistic fiction in the works by N. Gogol.